Strategic Optimization of Digital Business Models through SEO Implementation - Rahardja, Untung; Apriani, Desy; Faturahman, Adam; Ningrum, Fanani Islamia; Lachlan, Nicholas (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2026)
The development of technology and digital media has intensified competition among brands in establishing their presence in the digital space. This condition requires effective strategies to enhance brand awareness as a fundamental basis for building trust and brand recognition. Search Engine Optimization (SEO) is one of the strategic approaches that plays an important role in increasing brand visibility on search engines. This study aims to conceptually review the role of SEO in improving digital brand awareness. The study employs a literature review approach and conceptual analysis of the concepts, principles, and common practices of SEO in digital content management. The discussion focuses on the relationship between keyword optimization, content structure and quality, digital design, and information consistency with the level of brand exposure and recognition in the digital environment. The results of the conceptual review indicate that the implementation of SEO integrated with content strategy and digital design can enhance visibility, credibility, and audience recall toward a brand. Therefore, SEO functions not only as a search engine optimization technique but also as a strategic instrument for building and strengthening digital brand awareness sustainably in an increasingly competitive digital era.